Repetitive speech disorder resulting from infarcts in the paramedian thalami and midbrain. - Abe, K (1993)
A repetitive speech disorder resulting from infarcts in the paramedian thalami and the midbrain is reported. Although the speech disorder seemed like stuttering, the compulsive repetitions, constant rate and monotonous tone were not associated with ordinary stuttering. Since repetition was restricted to the first syllable, the speech disorder in our patient could be distinguished from palilalia. The extrapyramidal system is considered responsible for repetitive speech disorders resulting from infarcts in the paramedian thalami and the midbrain but without good reason. Repetitive speech disorder in patients with infarcts in the supplementary motor area (SMA) have similar clinical features to our patient. It is suggested that interruption in the projective system to the SMA is a possible cause of "stuttering like repetition".